Assessment of Fractal/Wrinkling Theories for Describing Turbulent Reacting Fine Structures under MILD Combustion Regimes. Issue 10 (27th July 2021) - Farokhi, Mohammadreza; Birouk, Madjid
ABSTRACT: This paper presents an assessment study of a modification introduced to a recently developed extended version of Eddy Dissipation Concept (EDC) chemistry/flow interaction approach for modeling Moderate or Intense Low-oxygen Dilution (MILD) combustion conditions. Compared to traditional combustion regimes, MILD combustion systems produce higher thermal efficiency and lower pollutant emissions. However, numerical simulation of turbulent flames under MILD combustion conditions poses challenges mainly due to strong coupling between turbulent flow and chemical kinetics over a wide range of turbulent flow conditions. Hence, combustion modeling is key for describing the interaction between chemistry and turbulent flow in MILD reacting flow regimes. This study examines the performance of a hybrid combustion approach (called hereafter wrinkling-EDC) which models the reacting scales of turbulent flows based on a fractal-based flame surface density and turbulent intermittency approaches in, respectively, premixed and diffusion flame regimes. Simulations are performed for two MILD combustion conditions of a Jet-in-Hot-Coflow burner, namely HM1 and HM3 flames, using wrinkling-EDC as well as the extended EDC. In addition, the results of the standard EDC model are provided for reference. The predictions of all three models are compared with their counterparts' experimental measurements of temperature and species concentrations. For both HM1 and HM3 flames, the results indicate that, compared to the standard and extended EDC approaches, the wrinkling-EDC model produces better predictions of the mixing field (close to the centerline of the burner) and temperature field. However, the predictions of all models become more comparable downstream of the burner. In addition, while all models produce comparable predictions of major species, intermediate and slow-forming species are best predicted downstream of the burner by the standard EDC model.